Reducing of Inconsistent Data using Fuzzy Multi Attribute Decision Making for Accessing Data from Database - Yusof, Mohd Kamir; Abdul Rahman, Mohd Nordin; Azlan, Atiqah (2013)
Inconsistent data in database occurs due to increasing number of data. A suitable technique is needed to reduce inconsistent data from database. In this paper, fuzzy multi attribute decision making was chosen to reduce inconsistent data from database. This technique contains 5 steps which are deriving quality vector, scale the quality matrix, compute weighted Euclidean distance and select final alternative. An application was developed using java and oracle technology. Sample data was selected for experiments purposes. The result indicates fuzzy multi attribute decision making is a suitable technique in reducing inconsistent data from database. Algorithm in fuzzy multi attribute decision making is able to find out a correct object.